1993
DOI: 10.1128/iai.61.8.3429-3439.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, nucleotide sequencing, and expression of the Clostridium perfringens enterotoxin gene in Escherichia coli

Abstract: A complete copy of the gene (cpe) encoding Clostidium perfingens enterotoxin (CPE), an important virulence factor involved in C. perfringens food poisoning and other gastrointestinal illnesses, has been cloned, sequenced, and expressed in Escherichia coli. The cpe gene was shown to encode a 319-amino-acid polypeptide with a deduced molecular weight of 35,317. There was no consensus sequence for a typical signal peptide present in the 5' region of cpe. Cell lysates from recombinant cpe-positive E. coli were sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 45 publications
7
41
0
2
Order By: Relevance
“…Consistent with previous reports demonstrating that CPE expression by type A isolates is strongly associated with sporulation (7,8,16), CPE-specific Western blotting detected no CPE expression during vegetative growth of the cpe-positive type A isolates F4406 and NCTC 10239 (data not shown) but showed that both of these cpe-positive type A strains (but not the cpe-negative type A strain ATCC 3624) produced moderate to high levels of CPE ( Fig. 2) when grown in Duncan-Strong sporulation medium supplemented with 1.5% bile and 0.005% theophylline (DS-B).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports demonstrating that CPE expression by type A isolates is strongly associated with sporulation (7,8,16), CPE-specific Western blotting detected no CPE expression during vegetative growth of the cpe-positive type A isolates F4406 and NCTC 10239 (data not shown) but showed that both of these cpe-positive type A strains (but not the cpe-negative type A strain ATCC 3624) produced moderate to high levels of CPE ( Fig. 2) when grown in Duncan-Strong sporulation medium supplemented with 1.5% bile and 0.005% theophylline (DS-B).…”
supporting
confidence: 92%
“…Combining these sequencing results with the CPE expression and Southern blot results presented above, it appears likely that our type E animal enteritis isolates and NCIB 10748 carry a single cpe sequence which is silent not only because it lacks promoters, a ribosome binding site, and an initiation codon but also because it contains numerous nonsense and frameshift mutations. This finding is remarkable given recent results (4,6,8) demonstrating that not a single base pair variation is present in the cpe ORF of eight different type A isolates, and it confirms that the mutations present in the silent NCIB 10748 cpe sequence are not simply an artifactual consequence of long-term laboratory cultivation.…”
Section: Fig 2 Western Immunoblot Analysis For Cpe Expression the supporting
confidence: 67%
“…Furthermore, densitometric analyses of these Western blots revealed that, under the growth conditions used in this experiment, CPE expression was ,®vefold higher in F4969 compared with SM101 (Table 1). Collectively, these results are consistent with previous studies (Czeczulin et al, 1993;1996;Kokai-Kun et al, 1994;Collie Q 1999 perfringens wild-type and cpe mutant strains. DNA prepared from wild-type (SM101 and F4969) and cpe mutant (MRS101 and MRS4969) C. perfringens strains was digested with HpaI, subjected to electrophoresis, blotted and probed separately with either cpe-speci®c or catP -speci®c DIG-labelled probes.…”
Section: Evaluation Of Cpe Expression By Cpe Knock-out Mutantssupporting
confidence: 93%
“…Silent cpe sequences, found near the iota toxin genes on episomal DNA, were highly conserved among type E isolates, but contained nine nonsense and two frameshift mutations and lacked the initiation codon, promoters, and ribosome binding site. This is remarkable, given that sequencing of cpe from eight different isolates revealed 100% sequence homology [19,[23][24][25]. These strains were apparently not clonal; location of cpe sequences, with iap and ibp, on episomal DNA and lack of isolate-specific mutations suggests recent wide distribution among C. perfringens isolates.…”
Section: Discussionmentioning
confidence: 93%